Modeling of nitrogen and sediment transport in Nagura River, Ishigaki City and That Luang wetlands, Vientiane City - Khamfeuane Sioudom (2008)
This study presents the results of applying the Soil and Water Assessment Tool (SWAT) model to model of nitrogen and sediment transport in Nagura River, Ishigaki City, Okinawa, Japan and That Luang wetlands, Vientiane City, Lao P.D.R., obtained by two research groups, namely, one based in Ishigaki City, Okinawa, Japan, and the other in the Vientiane City, Lao P.D.R. SWAT models water nutrients and sediment transport in rivers swamp and wetlands. Input data requirement are:1. Climate data (daily rainfall, max. and min. temperature, solar radiation, relative humility and wind speed) 2. Land cover and soil classes. 3. Topography (DEM). Point sources of nutrients. 5. Management practices for fertilizer application. The long term continuous hydrologic simulations were evaluated by comparing simulated daily and monthly average stream flows with daily and monthly observed stream flows at a set evenly distributed gauging stations. SWAT was applied to simulate hydrology, sediment and nutrient in Ishigaki City watershed, situated in Nagura River basin and Vientiane City watershed, situated in the Vientiane stream network system basin. The results herein are the "first-cut" preliminary analyses. For Ishigaki City, the following statistics were computed for flow simulations: (1) mean square error method (SSQ), expressed as a percent error bias (PBIAS), (2) Nash-Sutcliffe coefficient of efficiency (NSE), for values in a single year, first cumulatively for a one-year calibration period from day 1 to 365 for the year 2006, and then cumulatively for the entire one year simulation from this time series period for 2006. Model simulations of sediment transport were assessed by comparing graphical results of measured versus simulated constituent concentrations. A comparison of daily measured concentration versus simulated daily average suspended sediment concentration for the simulation period from day 1 to 365 for 2006 was made. For simulation at the drainage outlet, the SSQ of total average water flow was 0.14 m 3/s, which was caused by an underestimation of measured surface flow.The PBIAS value of -38.77% was computed for the watershed outlet in Kannda station westward of Ishigaki City, indicating a bias toward moderate overestimation. NSE was computed to be 0.53. Given that the NSE value is between 0.75 and 0.36, the simulation results are considered to be good. The overall evaluation of the SWAT model indicates that the model has the capability of fairly predicting surface runoff flow and sediment concentration for different soil. land use, s;opes and weather conditions. For Vientiane City, the following statistics for dimulated values of stream flow for a single year were computed : (1) mean square error method (SSG), expressed as a percent error bias (PBIAS), and (2) Nash-Sutcliffe coefficient of eefficiency. Simulated mpnthly stream flows were compared with observed month stream flows at five evenly distributed gauging stations; comulatively for a one-year simulation period from month Jan-2007 to Dec.-2007. Simulated monthly nitrate-nitrogen concentrations (NO3-N) were compared with observed monthly nutrient loads at one outlet watershed gauging station at Vientiane. However, for Vientiane there were numbers of scenarios involving different nutrient spatial and point source. The foloowing statistics were computed; (1) mean square error method (SSQ), expressed as a percent error bias (PBIAS) (2) Nash-Sutcliffe coefficient of efficiency, cumulatively overtake five-year calibration period starting from Jan-2000 to Dec.- 2004 (one year for flow). The same scenarios (P1, F1 and U1) were used for NH4-N loading simulation. Simulated monthly nitrogen concentrations (NH4-N) were compared with observed monthly nutrient loads at one evenly distributed outlet watershed gauging station. The SSQ of the scenarios for NH4-N loading was satisfactory whereas for PBIAS, only case P1 exhibited acceptable values. The other scenario over estimated ammonia loading. As for NSE, all scenarios displayed negative values. Fpr scenario 1 wherein the average daily precipitation for 2007 was used the model simulated accurately the observed flows for the simulation period for all the stations except Houakhua. The same can be said about the second scenario (20% higher rainfall), where only Houakhoau exhibited poor prediction for flow. And for scenario 3 (20% less rainfall), only one station predicted fairly accurate flows while stations the remaining three hust had satisfactory estimated flow. The Houakhoua station failed to have acceptable monthly flows for at any hence and for every scenario 2007. Only the scenarion with PO (no point source), FO (no fertilizer management practices) and UO (no residential high density) predicted NO3-N loading accurately with a SSQ value of 0.83 m3/s, PBIAS of 3.56% and NSE value of -0.19. The other thre scenarios namely there is only the point source (scenario 2, P1=point source), only the fertilizer application (scenarion 3, F1=fertilizer management practices) and there is only residential high density (scenario 4, U1= residential high density)exhibited more than 6 m3/s for SSQ and more than 150% PBIAS which indicate overestimation with respect to the observed values. They also showed fairly high negative NSE.
Identifying all relevant parameters was found to be essential to obtaining conclusive information about critical system processes and thence the formulation of management actions. Interactions between surface runoff volumes and within-channel processes were critical in describing the transport of sediments and nutrients in the study area. In relation to the objectives set in Chapter 1, the following conclusions are drawn: a) The SWAT model was able to simulate adequately the trends in stream flow, suspended sediment and nutrient loads. However, it still needs improvement in order to also predict the amount of ammonium-N (NH4-N) added to the soil from fertilizers (kg N/ha) or point sources as a water quality component.. b) In general, the simulated trends matched moderately well with the measured data. However, the model predicted some peaks in the stream flow which are not observed in the measured values. This could have led to some variations in the results and could be explained by inaccuracy in the input data and assumptions used the factors that did not produce the expected results, such as the runoff curve number, Manning's n value, channel/overland slope, lateral flow (days) and average slope length. The predicted peak runoff rates are overestimated, which could have led to variations in estimating the sediment loss in the Nagura River for long periods of time. c) Although surface runoff results were rated (error is between 15% and lessthan 25%), there were some deviations in the plot of certain parameters of up to 25%. The simulated nutrient results were dependent on the accuracy of hydrology and sediment calibration. The measured NO3-N concentration plot coincides with the predicted plots as attested by the -0.08% bias between the comparisons of simulation periods. The generated plots for NH4-N were not tested; because there is no available input data of NH4 for fertilizer applied to soil or point sources data types. d) For streamflow during the different periods of time: January 1 to December 31, 2006 for Ishigaki City and January 1 to December 31, 2007 for Vientiane City, all the predicted daily and monthly flow match well with the observed data. Given that the NSE coefficient ranges between 0.39 and 0.91, the simulation results are considered to be generally satisfactory. e) For Vientine City site: Using average daily precipitation input data for the model. Three different scenarios were run and analyzed to simulate average monthly surface flow. It is expected that better prediction would be obtained by varying rainfall spatially over the watershed. rainfall in the area originates mainly from convective storms over a contrasting landscape of lateral dimension significantly less than the length of the That Luang wetlands watershed. It is recommended that more rainfall stations be installed in the basin. For the computed NO3-N and NH4-N concentration with P1= point sources, F1=fertilizer application or U1= residential high density, the results of sensitivity analysis of NH4-N indicate that improved prediction of NH4-N can be obtained when additional input data for rainfall, point source, fertilizer management practices and residential high density are collected and made available for SWAT modeling. f) In general, the model demonstrated its utility as a useful tool in undertanding the processes occuring in the watersheds of Ishigaki City and Vientiane City, and as a basis to design and effective controls on stream flow, sediment and nutrients loads.
Vita.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Wetland hydrology -- Japan -- Okinawa; Wetland hydrology -- Laos -- Vientiane City; Hydrology -- Simulation methods; Hydrologic models; Simulation methods; Nagura River (Okinawa, Japan).; Ishigaki wetlands (Okinawa, Japan).; That Luang wetlands (Vientiane City, Laos).